1998
DOI: 10.1046/j.1365-2958.1998.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for structural diversity in the core regions of the lipopolysaccharides of Escherichia coli and Salmonella enterica

Abstract: SummaryBacterial lipopolysaccharides (LPS) are unique and complex glycolipids that provide characteristic components of the outer membranes of Gram-negative bacteria. In LPS of the Enterobacteriaceae, the core oligosaccharide links a highly conserved lipid A to the antigenic O-polysaccharide. Structural diversity in the core oligosaccharide is limited by the constraints imposed by its essential role in outer membrane stability and provides a contrast to the hypervariable O-antigen. The genetics of core oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
393
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(405 citation statements)
references
References 32 publications
9
393
0
3
Order By: Relevance
“…All of the mutants resistant to phage infection that we selected were related to the cell envelope. We confirmed that FhuA is the OM receptor, and we additionally found that the waaC and gmhD (earlier named rfaC and rfaD; Heinrichs et al, 1998) gene products are involved in phage infection.…”
Section: Introductionsupporting
confidence: 76%
“…All of the mutants resistant to phage infection that we selected were related to the cell envelope. We confirmed that FhuA is the OM receptor, and we additionally found that the waaC and gmhD (earlier named rfaC and rfaD; Heinrichs et al, 1998) gene products are involved in phage infection.…”
Section: Introductionsupporting
confidence: 76%
“…[29]. However, as patients' serum antibodies binding to EHEC LPS did not bind to the core of S. Urbana, this moiety of the core was not thought to be involved in antibody binding.…”
Section: Discussionmentioning
confidence: 92%
“…The R1, R2, R3, R4 and K-12 LPS core structures have been partially elucidated [17,29] and strains of E. coli with R3 core share an inner core sugar -3-deoxy-Dmanno-oct-2-ulsonic acid (Kdo) -with strains of Salmonella spp. [29].…”
Section: Discussionmentioning
confidence: 99%
“…One of the enzymes to which it is most similar is a galactosyltransferase (WaaX) responsible for addition of Gal in a b-1,4 configuration in the R4 subtype of E. coli COS (Heinrichs et al, 1998a). WaaX is a member of a family of b-glycosyltransferases that contains conserved motifs within the N-terminal 100 amino acids (Heinrichs et al, 1998b).…”
Section: Glycosyltransferasesmentioning
confidence: 99%